Steady water waves with vorticity: spatial Hamiltonian structure. (19th September 2013) - Kozlov, Vladimir; Kuznetsov, Nikolay
Abstract: Spatial dynamical systems are obtained for two-dimensional steady gravity waves with vorticity on water of finite depth. These systems have Hamiltonian structure and Hamiltonian is essentially the flow–force invariant.